Online Group Music-Making in Community Concert Bands: Perspectives From Conductors and Older Amateur Musicians - Barbeau, Audrey-Kristel; Generale, Mariane; Creech, Andrea (Frontiers in Psychology, 2022)
At the beginning of the pandemic, many music ensembles had to stop their activities due to the confinement. While some found creative ways to start making music again with the help of technologies, the transition from “real” rehearsals to “online” rehearsals was challenging, especially among older amateur musicians. The aim of this case study was to examine the effects of this transition on three community band conductors and three older amateur musicians. Specific objectives were to explore (1) intergenerational relationships to support online group music-making; (2) digital literacy and access in later life; and (3) online music-making in a Covid-19 context. Semi-structured interviews were conducted and theoretical thematic analysis was undertaken (Braun and Clarke 2006). Results were analyzed from the conductors’ and older musicians’ perspectives, and common trends were combined to facilitate interpretation. The first theme showed that being part of an intergenerational ensemble contributed positively to the learning experience online. The second theme demonstrated that because both conductors and musicians were new to the online rehearsals, it contributed to attenuate the age-related digital divide that may have been observed in other studies. Regarding access in later-life, older musicians reported benefits associated with rehearsing online, specifically in terms of distance/commute, time, energy, and cost. However, for those who did not already have internet and electronic devices, the cost of acquiring all the necessary equipment to make music online could have been too high. Finally, the third theme revealed that musicians appreciated the opportunity to make music online and indicated that it was definitely better than having nothing, especially for its social aspects. In conclusion, while participants noted several challenges associated with online music-making (e.g. zoom fatigue, technological issues), they were also appreciative of the opportunity to continue making music at a time when in-person rehearsals were not possible. Pedagogical implications are discussed, specifically the importance of the support network, of meeting people where they are, of learning to adapt, and of collaborative teaching.